Intrahepatic Cholestasis of Pregnancy - Jurk, Stanislaw M.; Kremer, Andreas; Schleussner, Ekkehard (Geburtshilfe und Frauenheilkunde, 2021)
Intrahepatic cholestasis of pregnancy (ICP) is a rare but potentially serious complication of pregnancy, the main symptom of which is intense pruritus with elevated serum levels of bile acids. The elevated serum bile acid concentration is regarded as a predictor for poor perinatal outcome including intrauterine death. Ursodeoxycholic acid (UDCA) has become established as the treatment of choice in clinical management to achieve a significant improvement in symptoms and reduce the cholestasis. Pregnant women with severe intrahepatic cholestasis should always be managed in a perinatal centre with close interdisciplinary monitoring and treatment involving perinatologists and hepatologists to minimise the markedly increased perinatal morbidity and mortality as well as maternal symptoms.
CRIS-Team WoS Importer:2021-09-03